The cAMP-ERK1/2 signaling pathway regulates urokinase-type plasminogen activator-induced bovine granulosa cell proliferation. Issue 6 (December 2020) - Zhao, Yufen; Yu, Boyang; Liu, Xinyu; Hu, Jitu; Yang, Yanyan; Namei, Erge; Yang, Bingxue; Bai, Yue; Qian, Yinghong; Li, Haijun
Abstract : Although urokinase-type plasminogen activator (PLAU) and urokinase-type plasminogen activator receptor (PLAUR) have been reported to play key roles in ovarian function, their precise contribution to mammalian follicular development remains unclear. In this study, we first observed that PLAU and PLAUR were present in bovine granulosa cells (GCs). Following culture of granulosa cells with PLAU (0.5 ng/mL) and PLAUR antibody (10 µg/mL) separately and together for 24 or 48 h, a proliferation assay showed that interaction between PLAU and PLAUR contributes to bovine GC proliferation. To study the potential pathways involved in PLAU/PLAUR-induced cell proliferation, ELISA and Western blotting were performed. We found that PLAU significantly increased the ratio of phosphorylated to non-phosphorylated ERK1/2 through PLAUR signaling. Further treatment with U0126, a specific ERK1/2 phosphorylation inhibitor, markedly suppressed PLAU/PLAUR-induced ERK1/2 phosphorylation and cell proliferation. In addition, we found that PLAU and PLAUR significantly increased the intracellular cAMP level and the use of Rp-cAMP, a specific PKA inhibitor, prevented PLAU/PLAUR from promoting activation of the ERK1/2 pathway and GC proliferation. Therefore, the interaction between PLAU and PLAUR may be involved in accumulating cAMP signals and enabling MAPK/ERK1/2 activation, affecting GC proliferation. Here, we provide new mechanistic insights into the roles of PLAU and PLAUR on promoting bovine GC proliferation. The finding that potential cross-points between PLAU/PLAUR-induced intracellular signals affect GC proliferation will help in understanding the mechanisms regulating early follicular development.